The Catholic Charismatic Renewal Through the Eyes of St. Thomas Aquinas. Issue 2 (April 2019) - Newton, William
The Catholic Charismatic Renewal has now passed its fiftieth birthday. Yet, it still seems very much on the fringes of the life of the Catholic Church. Perhaps one reason for this is that, for many Catholics, the Renewal appears to be, more or less, an innovation. One way to check the validity of that perception would be to take a look at the Renewal through the theology of one of the most mainstream of Catholic theologians, St. Thomas Aquinas. This is possible because Aquinas wrote about the charisms in a number of his works. The conclusion of this essay is that the key elements of the Renewal are conformable to the theological vision of St. Thomas. Nonetheless, there are a number of areas where Aquinas diverges from the standard interpretation of charismatic phenomena within the Renewal. This essay will side with Aquinas on some of these, but not all.